Pengaruh Gaya Kepemimpinan, Motivasi Dan Lingkungan Kerja Terhadap Loyalitas Karyawan (Studi Kasus Pada Dinas Perindustrian Dan Perdagangan Provinsi Sumatera Utara) - Dila Wulandari Batubara; Eka Purnama Sari (Journal of Creative Student Research, 2023)
Loyalty is someone's allegiance that indicates dedication to something, it can be a person or a group of people, ideals, tasks or goals that are given constantly. This study aims to determine whether leadership style, motivation and work environment have a partial and simultaneous influence on employee loyalty in the Department of Industry and Trade, and also among the three variables, which variable has the most dominant effect on the dependent variable. This type of research is quantitative research. This study uses secondary data, namely data on the number of employees for the last 5 years from the 2017-2021 period. The results of the analysis through the T test show that leadership style has no significant effect on employee loyalty, motivation has a significant effect on employee loyalty and work environment has a significant effect on employee loyalty. While the results of the analysis through the F test show that leadership style, motivation and work environment affect employee loyalty in the Department of Industry and Trade of North Sumatra Province.